KETERKAITAN DESENTRALISASI FISKAL SEBAGAI POLITICAL PROSESS DENGAN TINGKAT KEMISKINAN DI INDONESIA - Sebayang, Lesta Karolina (JEJAK: Jurnal Ekonomi dan Kebijakan, 2008)
This research aims to calculate fiscal capacity and estimate fiscal capacity, and poverty. Variableused in this research are fiscal capacities, Gross Regional Domestic Product (GRDP), and povertyvariable. Data used in this research is secondary sources from 25 Provinces in Indonesia with year timeperiod 1999 - 2003. This research limits its research object only 25 Provinces in Indonesia. In general,this paper concludes that Gross Regional Domestic Product (GRDP) and fiscal capacity have an effecton significant statistically to poverty, its meaning that fiscal capacity in 25 the provinces can expressability to improve economic growth. Government policy in APBD as political process influence fiscalcapacities, economic growth, and poverty in Indonesia. Recomendation from this research are localgoverment must concern about fiscal capacity end Regional Domestic Product (GRDP) end govermenttry to increase responsibility so all of country can improve their wealth.Keywords: Fiscal capacity, Gross Regional Domestic Product (GRDP), poverty, fiscal policy